Orientalism, Balkanism and Europe's Ottoman heritage. (July 2019) - Bryce, Derek; Čaušević, Senija
Abstract: 'Orientalism' has been used as a lens to understand consumption of heritage sites in non-Western contexts. Through the supplementary lens of 'Balkanism', we examine a European region with a significant heritage reflecting the c.500 year rule of the Ottoman Empire. Bosnia and Herzegovina, Republic of North Macedonia and Albania are selected for study given their concentration of Ottoman heritage sites. We note first that these countries' heritage tourism sectors anticipate and modify interpretation to accommodate 'Western' tourists' affectation of 'surprise' and 'delight' at a 'remarkable' crossroads between 'West/East' or 'Christendom/Islam'. To understand why Ottoman heritage is often understood to be in but not of Europe, our analysis draws on scholarship interrogating 'Europe's' longstanding discursive erasure of its Ottoman-Islamic-Oriental 'self' and Tourism's role in this. Highlights: Interrogates Said's notion of 'Orientalism' within a European context. Contextualises the above in Heritage Tourism in the Balkans. Raises the profile of critical question on Ottoman heritage and European identity.